Pragmatic and Semiotic Studies: A New Perspective on Bakaran Batik Legend Motif, Juana District, Pati Regency, Indonesia - Supriyadi, Slamet; Ismail, Abd Rasid; Yunianti, Esterica (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2024)
As an ancient Indonesian art, Batik has been recognized by the United Educational Scientific and Cultural Organization (UNESCO). Batik is one of the original handicrafts in Indonesia. This research explores three main issues of Bakaran batik legend: community leaders’ viewpoint in Juana, Pati Regency; aspects of context and implicatures; and coherences among themes, visual elements, and images. A qualitative method was conducted in this research. It was conducted in February-April 2022 with a case study at Bakaran Juana Pati district. Data collection techniques were employed through in-depth interviews, non-participatory observation, and document analysis. Data was collected using observations and interviews with eight informants. The data was analyzed using pragmatics. The findings revealed that Bakaran batik has its uniqueness explicitly in its patterns. Numerous designs in Bakaran batik patterns are associated with the legend of Nyai Ageng Danowati, a Majapahit Kingdom’s Batik expert figure who escaped from Majapahit and then lived in Bakaran village Juana district, Pati Regency. It implicitly has legendary aspects when analyzed in terms of possible patterns. Bakaran village’s legendary patterns include the Kembang Druju, the Limaran, the Gandrung, and the Magel Ati. The legend pattern’s context is typically connected with the legend of the Batik figure, Nyai Ageng Danowati, and the implicature of the legendary pattern is related to the moment of Nyai Ageng Danowati for spending her life while she was on the escapement. The visual elements and the image of the legend motif are coherent, and the visual form of the Motif theme is relevant to Nyai Danowati’s life story.